2021
DOI: 10.7759/cureus.14346
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Evidence of Complete Transection of the Lumbar Sympathetic Trunk After Extreme Lateral Transpsoas Approach to the Lumbar Spine: A Word of Caution

Abstract: Iwanaga et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These are located in the extraperitoneal connective tissue on the anterolateral surface of the lumbar spine, along the medial edge of the psoas major (Murata et al, 2003; Standring, 2016). Iwanaga, Zeoli, et al (2021) reported a case where an experienced spine surgeon demonstrated a far lateral interbody fusion operation on a cadaver. After the operation, the lumbar sympathetic nerve was completely transectedat the L3 vertebral body level.…”
Section: Discussionmentioning
confidence: 99%
“…These are located in the extraperitoneal connective tissue on the anterolateral surface of the lumbar spine, along the medial edge of the psoas major (Murata et al, 2003; Standring, 2016). Iwanaga, Zeoli, et al (2021) reported a case where an experienced spine surgeon demonstrated a far lateral interbody fusion operation on a cadaver. After the operation, the lumbar sympathetic nerve was completely transectedat the L3 vertebral body level.…”
Section: Discussionmentioning
confidence: 99%